2018
DOI: 10.3389/fnut.2018.00118
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Variation in Consumption Patterns of Sustainable and Nutritious Seafood in Australia

Abstract: National dietary guidelines (DGs) consistently recommend consuming seafood for health benefits, however, the sustainability of increasing seafood consumption is often challenged. Seafood products vary in environmental performance as well as health benefits, yet there is no information integrating the health and ecological impacts of different seafood choices. The first step in optimising improved health and environmental outcomes is to examine more closely the types of seafood being consumed at population and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 74 publications
(82 reference statements)
4
16
0
1
Order By: Relevance
“…An increasing amount of literature focuses on fish consumption and diet sustainability [ 49 , 50 , 51 , 52 ]. In our research, nearly 70% of the population, regardless of age or gender, stated that fish and derivatives are linked to a sustainable diet.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of literature focuses on fish consumption and diet sustainability [ 49 , 50 , 51 , 52 ]. In our research, nearly 70% of the population, regardless of age or gender, stated that fish and derivatives are linked to a sustainable diet.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used here build on a recent sociodemographic analysis of fish consumption patterns in Australia [41] in three important ways. Firstly, we adjust for potential underreporting of total energy intake by participants, which is common in all nutrition surveys and is important when trying to estimate the true impact of seafood consumption throughout the food system.…”
Section: Methodsmentioning
confidence: 99%
“…In an analysis of NHANES 2011-2014 data, overall supplement use by adults was higher in participants who were well above the poverty level, were food-secure, and did not participate in SNAP (Supplemental Nutritional Assistance Program)-regardless of age, gender, and ethnicity [34]. A similar trend has also been illustrated in Australia, where an analysis of the national Australian Health Survey revealed that unemployed citizens with less educational attainment tended to consume less fish overall, with a higher proportion of fish that are lower in n-3 LCPUFA content, when compared to higher-educated, higher-earning counterparts [35]. This pattern may be attributed to many factors, including lack of access to information concerning proper nutrition, as well as an overall lack of resources.…”
Section: Discussionmentioning
confidence: 65%